The Importance of Research for the Aspiring Young Scientists - Villela, Ricardo (International Journal of Clinical Research, 2022)
For many years, research served as the primary pillar behind the growth of medical sciences and provided the scientific community with the tools needed to expand their discoveries. According to a recent survey, students are now unable to follow research tracks owing to financial difficulties, obstacles in finding opportunities, or a lack of enthusiasm in research due to insufficient exposure to medical research in their medical schools. This becomes a worrisome fact since medical school curricula are not giving much importance to research in the training of future medical generations. This editorial tackles these challenges and how to face them.